Archaeobotany in central Argentina: macro- and microscopic remains at several archaeological sites from early Late Holocene to early colonial times (3,000–250 bp) - Lopez, María Laura (2018)
Recent archaeobotanical research on 16 archaeological sites in the Sierras de Córdoba, central Argentina, provides new insights into the livelihoods and subsistence practices of the peoples who inhabited this mountainous region from c. 3,000–250 bp. Significantly, the plant macro- and microbotanical remains, identified as primarily fruit from wild trees, crops and weeds, provide evidence for a continuation in the consumption and manipulation of plant resources. During the late pre-Hispanic period (1,500–350 bp) people used domesticated plants such as maize, as well as new types of plant processing techniques that permitted the consumption of otherwise inedible wild seeds such as chenopods. The introduction of cultivated plants through contact with agricultural societies at around 1,000 bp was slow and did not substantially change the existing foraging way of life. Instead, crop plants were added to the existing, highly diversified subsistence systems in use in the Sierras de Córdoba, rather than replacing wild plant gathering.